Endogenous Protective Factors and Potential Therapeutic Agents for Diabetes-Associated Atherosclerosis - Wang, Chaoqun; Chen, Jin; Wang, Pin; Qing, Shengli; Li, Wenwen; Lu, Jin (Frontiers in Endocrinology, 2022)
The complications of macrovascular atherosclerosis are the leading cause of disability and mortality in patients with diabetes. It is generally believed that the pathogenesis of diabetic vascular complications is initiated by the imbalance between injury and endogenous protective factors. Multiple endogenous protective factors secreted by endothelium, liver, skeletal muscle and other tissues are recognized of their importance in combating injury factors and maintaining the homeostasis of vasculatures in diabetes. Among them, glucagon-like peptide-1 based drugs were clinically proven to be effective and recommended as the first-line medicine for the treatment of type 2 diabetic patients with high risks or established arteriosclerotic cardiovascular disease (CVD). Some molecules such as irisin, lipoxins have recently been perceived as new protective factors on diabetic atherosclerosis, while the protective role of HDL has been reinterpreted since the failure of several clinical trials to raise HDL therapy on cardiovascular events. The current review aims to summarize systemic endogenous protective factors for diabetes-associated atherosclerosis and discuss mechanisms as well as potential therapeutic strategy of them or their analogues. In particular, we focus on the existing barriers or obstacles that need to be overcome in developing new therapeutic approaches for macrovascular complications of diabetes.